Recovery of lycopene from industrially derived tomato processing by-products by pulsed electric fields-assisted extraction. (July 2020) - Pataro, G.; Carullo, D.; Falcone, M.; Ferrari, G.
Abstract: The influence of pulsed electric fields (PEF) pre-treatment at different field strength (E = 1–5 kV/cm) and energy input (WT = 5–10 kJ/kg) on the recovery yield of lycopene in either acetone or ethyl lactate from industrial tomato peels residues, was investigated. The rate of lycopene extraction in both solvents decreased with time and was predicted rather satisfactorily (R 2 = 0.96–0.99) by the Peleg's model. Micrograph of tomato peels showed that PEF induced size reduction and separation between the plant cells likely due to pore formation and leakage of intracellular matter. Coherently, PEF treatment (5 kV/cm, 5 kJ/kg) significantly enhanced the extraction rate (27–37%), the lycopene yields (12–18%) and the antioxidant power (18.0–18.2%) in either acetone and ethyl lactate extracts, as compared with untreated samples. However, acetone gave the highest lycopene yield. HPLC analyses revealed that all-trans lycopene was the main carotenoid extracted and no degradation/isomerization phenomena occurred. The results obtained in this work suggest that the application of PEF prior to solid-liquid extraction with environmentally friendly solvents could represent a sustainable approach for the valorization of industrial tomato peels residues. Industrial relevance: Industrial processing of tomatoes generates large amount of by-products, mainly peels, which represent a cheap and abundant source of natural carotenoids, especially lycopene. The recovery lycopene from tomato peels residues is a crucial step for use in a wide range of industrial applications in food, cosmetic and pharmaceutical sectors as natural pigment and antioxidant. PEF pre-treatment allows to intensify the extractability of lycopene from of tomato processing by-products using environmentally friendly solvents, thus adding new value to the tomato processing chain, improving economic performances and decreasing waste problems. Graphical abstract: Unlabelled Image Highlights: Lycopene extraction kinetic is well fitted by Peleg's model. Acetone allows to extract lycopene more effectively than by ethyl lactate. PEF induces size reduction and separation between the plant cells. PEF pre-treatment intensifies the extractability of lycopene from tomato peels. All-trans lycopene is the most abundant carotenoid in tomato peels extracts.